Teachers' Competence in Developing Teaching Modules through In-House Training (IHT) at Madrasah Ibtidaiyah - Sri Wahyuni; Sabar Narimo; Achmad Fathoni (AL-ISHLAH: Jurnal Pendidikan, 2025)
Elementary school teachers, particularly in Madrasah Ibtidaiyah, face challenges in developing character-based teaching modules due to limited relevant training. This study aimed to enhance teacher competence through in-house training (IHT) integrated with intensive mentoring and digital technology. A qualitative case study was conducted at a Madrasah Ibtidaiyah in Kebakkramat, Karanganyar, involving 10 teachers, supported by the principal and school supervisor. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The IHT program significantly improved teachers' competence in designing character-based teaching modules aligned with the Merdeka Curriculum. Findings showed that 80% of participants understood the structure of teaching modules, 70% could align learning outcomes and objectives with activities and assessments, and 80% successfully compiled contextual and systematic modules. All participants benefited from peer feedback and facilitator guidance, while 90% reported increased confidence in implementation. The integration of digital tools such as Google Docs, Canva, and collaborative platforms further supported the training's effectiveness. The study demonstrates that a structured IHT model, combining practical mentoring and technology use, effectively builds both technical and pedagogical competencies. These findings contribute to national efforts in developing adaptive, tech-literate teachers capable of delivering student-centered learning. However, the study's limitations include its small sample size and single-school context. Future research should explore broader implementation with continuous mentoring and strengthened digital reflection practices to ensure sustainable professional development.